Benefits and Challenges of Using Digital Multimodal Texts: A Case Study of Two EFL Teachers - Sabila Agnia; Rahma Sakina; Sri Yunita (Ma'soem University, 2026)
The integration of digital technology in education has encouraged teachers to adopt innovative approaches that support students’ learning needs. One such approach is the use of digital multimodal texts, which combine visual, audio, video, and textual elements to enhance learning experiences. While previous studies have mainly focused on students’ perspectives, limited research has explored teachers’ views in Indonesian EFL contexts. This study aimed to investigate English teachers’ perceptions of digital multimodal texts and identify the benefits and challenges of their implementation in English language teaching. Using a descriptive qualitative design, data were collected through a pre-interview reflective checklist and follow-up semi-structured interviews with two English teachers at SMA Al-Ma'soem, West Java, Indonesia.. The findings revealed that teachers held positive perceptions toward the use of digital multimodal texts. They reported that digital multimodal texts enhanced students’ motivation, creativity, critical thinking, and comprehension while accommodating diverse learning styles. However, challenges related to internet connectivity and technical difficulties during the initial implementation were also identified. The study highlights the importance of adequate technological infrastructure and continuous professional development to support the effective integration of digital multimodal texts in EFL classrooms.